Writing for the media - Ashton, Philip; Image Link (Bendigo, Victoria : Produced by Image Link for Video Education Australasia, 1993)
This program goes to the experts in order to discover how to write an effective press release, get a letter into the paper, prepare for radio talkback, write a news story or feature, write for the spoken word of radio and television and offer criticism to the media.
Narrator: Claudia Sobolewsky, Anna Ashton.
Keywords: Journalism -- Authorship; Feature writing; Broadcast journalism